Protein phosphorylation networks in Baylisascaris procyonis revealed by phosphoproteomic analysis - Qin Meng; Zhikang Li; Qiguan Qiu; Shuyu Chen; Haiyan Gong; Xiaoruo Tan; Xiaoheng Liu; Zhaoguo Chen; Wei Liu (Parasites & Vectors)
Abstract Background Baylisascaris procyonis is an intestinal ascarid worm that parasitizes in raccoons and causes fatal neural, visceral, and ocular larva migrans in humans. Phosphorylated proteins and protein kinases have been studied as vaccine and drug target candidates against parasitic infections. However, no data are available on protein phosphorylation in the raccoon roundworm. Methods In this study, the entire proteome of adult B. procyonis was enzymatically digested. Then, phosphopeptides were enriched using immobilized metal affinity chromatography (IMAC) and analyzed by liquid chromatography-mass spectrometry (LC-MS/MS). Results Our phosphoproteome analysis displayed 854 unique phosphorylation sites mapped to 450 proteins in B. procyonis (3308 phosphopeptides total). The annotated phosphoproteins were associated with various biological processes, including cytoskeletal remodeling, supramolecular complex assembly, and developmental regulation. The phosphopeptide functional enrichment revealed that B. procyonis phosphoproteins were mostly involved in the cytoskeleton cellular compartment, protein binding molecular function, and multiple biological processes, including regulating supramolecular fiber and cytoskeleton organization and assembling cellular protein-containing complexes and organelles. The significantly enriched pathways of phosphoproteins included the insulin signaling pathway, tight junction, endocytosis, longevity-regulating, glycolysis/gluconeogenesis, and apelin signaling pathways. Domain analysis revealed that the Src homology 3 domain was significantly enriched. Conclusions This study presents the first phosphoproteomic landscape of B. procyonis, elucidating phosphorylation-mediated regulation of cytoskeletal dynamics, host interaction pathways, and metabolic adaptations. The identified 450 phosphoproteins and enriched functional domains establish a foundation for targeting conserved mechanisms critical to B. procyonis survival. Graphical Abstract